Addition of Black Cumin in Stevia Apple Jam and to Check Effect on its Nutrition Profile on Storage - Khawar Ali, Muhammad Imtiaz Khan, Muhammad Akram, Mansoor Ali, Javed Ahmed Ujjan, Fahim Haider Jamali, Kiran Sitara, Tahir Iqbal, Zulfiqar Ali, Nadia Saeed, Qasim Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stevia is nontoxic and non-caloric sweetens nearly 300 times more sweetener than any other source. Numerous health benefits for chronic patients and its reach source of essential nutrients pooling the world. Objective: This study tried analyzed the effect of black cumin added in stevia apple jam in place of sugar as functional ingredient due to health promoting effects in case of hypertension. Method: A stevia-sweetened apple jam sample was mixed with black cumin. And the effect was measured and recorded by sensory evaluation and proximate analyses over a six-month period. Practical implication Conclusion: Finding revealed that black cumin contained stevia apple jam significantly increased the total suspended solid level while, decreased moisture contents in sampled experiment. Unlikely, it increased nutritional components such as proteins, carbohydrates and fat due to black cumin addition. Thus, black cumin in stevia apple jam paramount important with magnifying essential nutrients for current novel chronic disease remedy. Keywords: Stevia, Black cumin, Nutrition, Jam, Hypertension, chronic disease,